Investigation of a radiative sky cooling module using phase change material as the energy storage. (1st September 2022) - Kiyaee, Soroush; Khalilmoghadam, Pooria; Behshad Shafii, Mohammad; Moshfegh, Alireza Z.; Hu, Mingke
Highlights: The nocturnal radiative cooling potential of a trifunctional module is introduced. The PCM tank keeps the temperature below the minimum 24 h ambient temperature. The exergy efficiency calculation of radiative sky cooling systems is proposed. A comparison of various PCMs is performed to find the optimal storage temperature. Abstract: Radiative sky cooling (RSC) systems have enjoyed a privileged position in the research community due to generating cooling energy without consuming electricity using the open atmospheric window and infrared emission to the sky. However, the system's justification occurs when it reaches a temperature below the minimum 24-hour ambient temperature. This study utilizes phase change materials (PCM) as the energy storage of a hybrid daytime photovoltaic-thermal and nighttime RSC module and investigates the nocturnal cooling energy-saving potential of the system at different phase transition temperatures. After being validated by the experimental data in the literature, the simulated model was used for examining the exergy and energy efficiencies of PCMs with varying phase transition temperatures. The comparison of the exergy efficiency in the radiative sky cooling systems was performed for the first time, revealing the simultaneous effect of the temperature drop and cooling power to specify the optimal operative point of the system. Based on the climatic conditions of the simulation site, the PCM with phase transition temperatures of 18 °C revealed the peak and average exergy efficiencies of 42.8% and 33.7%, respectively. Likewise, the 23 °C PCM recorded the maximum cooling power of about 49.9 W/m 2, and the 15 °C PCM achieved the highest temperature drop of about 14.8 °C.